2003
DOI: 10.1128/jcm.41.9.4395-4399.2003
|View full text |Cite
|
Sign up to set email alerts
|

Comparing First-Void Urine Specimens, Self-Collected Vaginal Swabs, and Endocervical Specimens To DetectChlamydia trachomatisandNeisseria gonorrhoeaeby a Nucleic Acid Amplification Test

Abstract: We set out to determine the prevalences of Chlamydia trachomatis and Neisseria gonorrhoeae by ligase chain reaction as well as to determine the prevalence of Trichomonas vaginalis by culture in a large and diverse national sample of non-health-care-seeking young women entering the military; we also sought to compare the abilities of three different techniques of collecting specimens (first-void urine, self-collected vaginal swab, and clinician-collected endocervical swab) to identify a positive specimen. A cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
78
0
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(89 citation statements)
references
References 30 publications
(22 reference statements)
7
78
0
4
Order By: Relevance
“…La diagnosi di infezione da C.t., basata sull'utilizzo del tampone vaginale, si attesta su livelli di efficacia pari o superiori ai più tradizionali mezzi di indagine mediante coltura ed ai più moderni metodi di indagine mediante tecniche di amplificazione su campioni di urine o tamponi cervicali. Diversi studi (96,103) hanno confermato la validità dell'autoprelievo vaginale confrontato con prelievi endocervicali e vaginali eseguiti da personale specializzato dimostrando rispettivamente una sensibilità del 100% ed una specificità del 98.5%. L'alta sensibilità dei NAATs permette inoltre di utilizzare "pools" di campioni per ridurre i costi.…”
Section: Metodi Immunoenzimatici (Eia)unclassified
“…La diagnosi di infezione da C.t., basata sull'utilizzo del tampone vaginale, si attesta su livelli di efficacia pari o superiori ai più tradizionali mezzi di indagine mediante coltura ed ai più moderni metodi di indagine mediante tecniche di amplificazione su campioni di urine o tamponi cervicali. Diversi studi (96,103) hanno confermato la validità dell'autoprelievo vaginale confrontato con prelievi endocervicali e vaginali eseguiti da personale specializzato dimostrando rispettivamente una sensibilità del 100% ed una specificità del 98.5%. L'alta sensibilità dei NAATs permette inoltre di utilizzare "pools" di campioni per ridurre i costi.…”
Section: Metodi Immunoenzimatici (Eia)unclassified
“…[2][3][4][5] However, evidence indicates that SAVS may perform better than urine samples. [6][7][8] Knox et al 8 used PCR for SAVS and first-void urines (FVU) and found that SAVS were more sensitive for C. trachomatis and N. gonorrhoeae. Shafer et al 7 compared FVU, SAVS, and PACS and found that SAVS detected the highest number of positive cases for C. trachomatis and N. gonorrhoeae from a single specimen.…”
Section: 8-10mentioning
confidence: 99%
“…[6][7][8] Knox et al 8 used PCR for SAVS and first-void urines (FVU) and found that SAVS were more sensitive for C. trachomatis and N. gonorrhoeae. Shafer et al 7 compared FVU, SAVS, and PACS and found that SAVS detected the highest number of positive cases for C. trachomatis and N. gonorrhoeae from a single specimen. Of note, a study investigating the feasibility of STI screening in the ED by urine testing found that 15% of eligible patients were not screened because they could not provide a urine sample.…”
Section: 8-10mentioning
confidence: 99%
See 1 more Smart Citation
“…Self-collected vaginal samples may be as accurate as clinician-obtained specimens for diagnosing various sexually transmitted infections including Neis-seria gonorrhea, Chlamydia trachomatis, Trichomonas vaginalis, and human papillomavirus. [7][8][9][10][11][12][13] Moreover, self-sampling the vagina seems to be very acceptable to women of multiple ethnic groups. 8,9,[13][14][15][16][17] Women have also demonstrated a willingness to obtain a self-sample of vaginal secretions for Gram stain detection of bacterial vaginosis.…”
mentioning
confidence: 99%